TRANSONIC TURBINE BLADE TIP AERO-THERMAL PERFORMANCE WITH DIFFERENT TIP GAPS: PART I - TIP HEAT TRANSFER - Zhang, Q; O'Dowd, DO; He, L; Oldfield, M; Ligrani, P; ASME (2010)
A closely combined experimental and CFD study on a transonic blade tip aero-thermal performance at engine representative Mach and Reynolds numbers (Mexit=1, Reexit=1.27x106) is presented in this and its companion paper (Part II). The present paper considers surface heat transfer distributions on tip surfaces, and on suction and pressure side surfaces (near-tip region). Spatially-resolved surface heat transfer data are measured using infrared thermography and transient techniques within the Oxford University High Speed Linear Cascade research facility. The Rolls-Royce PLC HYDRA suite is employed for numerical predictions for the same tip configuration and flow conditions. The CFD results are generally in good agreement with experimental data, and show that the flow over a large portion of the blade tip is supersonic for all three tip gaps investigated. Mach numbers within the tip gap become lower as the tip gap decreases. For the flow regions near the leading edge of the tip gap, surface Nusselt numbers decrease as the tip gap decreases. Opposite trends are observed for the trailing edge region. Several 'hot spot' features on blade tip surfaces are attributed to enhanced turbulence thermal diffusion in local regions. Other surface heat transfer variations are attributed to flow variations induced by shock waves. Flow structure and surface heat transfer variations are also investigated numerically when a moving casing is present. The inclusion of moving casing leads to notable changes to flow structural characteristics and associated surface heat transfer variations. However, significant portions of the tip leakage flow remain transonic with clearly identifiable shock wave structures. Copyright © 2010 by ASME.